2017
DOI: 10.3126/jnhrc.v15i2.18203
|View full text |Cite
|
Sign up to set email alerts
|

Morbidities and Outcome of a Neonatal Intensive Care in Western Nepal

Abstract: Background: Neonatal mortality rate of developing countries is declining over decades. In the recent years increasing number of preterm and high risk neonates have facilities for tertiary care treatment. The aim of the study was to assess the morbidities and outcome of neonatal intensive care admissions.Methods: It was a retrospective observational study carried out in neonatal intensive care unit of the Manipal Teaching Hospital, Pokhara, Nepal from January 2014 to December 2015. Neonatal details including pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
2
10
0
1
Order By: Relevance
“…The reasons stated were their domicile in another region, had other children at home, and dissatisfaction towards the treating physician. 12 The other reasons for DAMA in this study were a lack of improvement (21%) and the belief of significant improvement (12%). This is also worrisome as there is clearly a lapse in perceiving the severity of illness of newborns among family members.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The reasons stated were their domicile in another region, had other children at home, and dissatisfaction towards the treating physician. 12 The other reasons for DAMA in this study were a lack of improvement (21%) and the belief of significant improvement (12%). This is also worrisome as there is clearly a lapse in perceiving the severity of illness of newborns among family members.…”
Section: Discussionmentioning
confidence: 71%
“…However, other authors from various tertiary centers of Nepal have reported the incidence of DAMA to be 2-12%. [9][10][11][12] This discrepancy should be taken in the context of variations in local socio-cultural beliefs, services offered by the institutions, and different time scale of studies. In other developing countries like ours, the prevalence of DAMA varies from 11.1-25.4% of total admissions in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from various parts of country showed high variability of neonatal mortality ranging from 3.32% -24.74%. 6,11 Likewise similar type of variation in neonatal mortality were observed in different countries which ranged from 7.16% -36.6%.¹ [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These variabilities in mortality within the country and also outside might be due to various reasons including severity of illness during admission, time lapse between illness and hospital arrival, percentage of extramural cases, availability of medical equipment and skill of the medical experts.…”
Section: Discussionmentioning
confidence: 87%
“…Male babies being predominant in both hospital admissions (77.35%) as well as in poor outcomes, (22.65%) raise the issues of biological vulnerability of male neonates, similar finding were observed in other studies. [6][7][8][9][10][11][12] Neonates born to young mothers who were less than 20 years have highest mortality rate which is statistically significant (p-value 0.002). This might be due to poor nutritional status, low maternal education, lack of family support, abs ence of antenatal checkup and poor socioeconomic condition.…”
Section: Discussionmentioning
confidence: 98%
“…Increased GGT levels are associated with poor outcomes in sepsis and cardiovascular diseases in adults [ 1 , 2 , 3 , 4 , 5 , 6 ]. Sepsis is also universally accepted as a risk factor in ICUs [ 15 ]. GGT is considered as a predictor for diseases involving oxidative stress and inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%